2002
DOI: 10.1016/s0048-7333(01)00125-1
|View full text |Cite
|
Sign up to set email alerts
|

Market versus technology drive in R&D internationalization: four different patterns of managing research and development

Abstract: Research and development are subject to different location drivers. The analysis of 1021 R&D units, each distinguished by its main orientation towards either research or development work, reveals that research is concentrated in only five regions worldwide, while development is more globally dispersed. Our research is based on 290 research interviews and database research in 81 technology-intensive multinational companies. We identify two principal location rationales-access to markets and access to science-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
290
0
39

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(335 citation statements)
references
References 31 publications
6
290
0
39
Order By: Relevance
“…On the one hand, empirical studies analyzing the R&D outsourcing decisions by technological firms tended to overlook the location dimension (Afuah, 2001;Hitt et al, 1998;Leiblein & Miller, 2003;Mayer & Salomon, 2006;Mol, 2005;Narula, 2001;Pisano, 1990;Veugelers & Cassiman, 1999). On the other, those studies more focused on the location decision either tended to analyze only FDI or internal modes of governance (captive offshoring) (Belderbos, 2001;Berry, 2006;Bunyaratavej et al, 2007;Cantwell, 1995;Demirbag & Glaister, 2010;Doh, Bunyaratavej, & Hahn, 2009;Kuemmerle, 1999;Odagiri & Yasuda, 1996;Piscitello & Santangelo, 2010;von Zedwitz & Gassmann, 2002) or to analyze the offshoring phenomenon in the aggregate without distinguishing between internal (captive offshoring) and external (outsource offshoring) modes of governance (Dossani & Kenney, 2003;Lewin & Couto, 2007;Lewin et al, 2009;Manning et al, 2008;Mudambi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, empirical studies analyzing the R&D outsourcing decisions by technological firms tended to overlook the location dimension (Afuah, 2001;Hitt et al, 1998;Leiblein & Miller, 2003;Mayer & Salomon, 2006;Mol, 2005;Narula, 2001;Pisano, 1990;Veugelers & Cassiman, 1999). On the other, those studies more focused on the location decision either tended to analyze only FDI or internal modes of governance (captive offshoring) (Belderbos, 2001;Berry, 2006;Bunyaratavej et al, 2007;Cantwell, 1995;Demirbag & Glaister, 2010;Doh, Bunyaratavej, & Hahn, 2009;Kuemmerle, 1999;Odagiri & Yasuda, 1996;Piscitello & Santangelo, 2010;von Zedwitz & Gassmann, 2002) or to analyze the offshoring phenomenon in the aggregate without distinguishing between internal (captive offshoring) and external (outsource offshoring) modes of governance (Dossani & Kenney, 2003;Lewin & Couto, 2007;Lewin et al, 2009;Manning et al, 2008;Mudambi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alcacer´ and Zhao (2012) showed that strong internal linkages help firms increase internalization and create higher levels of technological in-terdependence across firm locations and a good relationship with the local institutions. On this point, Von Zedtwitz and Gassmann (2002) conclude that companies decentralize research to take advantage of proximity to univer-sities and centers of innovation, access to science communities, or to make up for a limited domestic science base. Kuemmerle (1999) uses a logistic regression and finds that a firm's propensity to establish activities increases with its relative commitment to a country, the educational attainment of the labor pool, and the country's scientific achievement.…”
Section: Rational Model Studiesmentioning
confidence: 99%
“…Adner and Levinthal (2001) mentioned that product development becomes a way of maintaining product value. Zedtwitz and Gassmannb (2002) stated that products enterprises with an important R&D department are either in a strong dominant design position in its main technologies or their principal market is helpful to fit consumer's demand and satisfaction. They also pointed out that technologyoriented R&D product development departments will be employed to develop new products.…”
Section: Research Background and Motivesmentioning
confidence: 99%